Seismotectonic, Potential Seismic and Volcano Hazard of Minahasa Peninsula, Eastern Indonesia - Asdani Soehaimi; Tatang Padmawidjaja; S.R Sinung Baskoro; Fitriani Agustin; Mohamad Ridwan (Jurnal Geologi dan Sumberdaya Mineral, 2022)
The Minahasa Peninsula is located in the western flank of Mollucca seismotectonic zone existed, where are four active tectonic plates colliding from east to west are the Philippine Oceanic Plate, Halmahera Micro Continental Plate, Mayu Ridge Micro Oceanic Slab Plate and the Minahasa Peninsula Micro Continental Plate. The result of the probabilistic seismic hazard assessment in Manado City and surrounding area, Zone I (site class SE), Zone II (site class SD) and Zone III (site class SC), shows the building and non building for risk category I, II, III and IV, has the seismic disign category D. Building and non building in Zone I (SD1=0,80g) with risk category I, II, III has structure seismic design category E and risk category IV has seismic design category F.The correlation of seismotectonic, structural geology, and seismicity to the volcanic centers distribution in this region, shows the Minahasa Peninsula volcanoes can be divided into two regions are the compressional and extentional volcanoes tectonic regions. To mitigate the seismic risk in this region, the structure for building and non building contraction is recommended to follow the procedures for planning earthquake resistance for building structures and non building (BSN, SNI 1726-2019). On another hand, for potential volcano hazard, recommended followed the guidance map of the volcanic hazard prone region by The Center for Volcano and Geological Hazard Mitigation, Geological Agency of Indonesia.Keywords: Mollucca seismotectonic zone, potential seismic and volcanoes hazard.